Characterization of neutrophil function in Papillon-Lefèvre syndrome. Issue 2 (8th March 2016) - Roberts, Helen; White, Phillipa; Dias, Irundika; McKaig, Sarah; Veeramachaneni, Ratna; Thakker, Nalin; Grant, Melissa; Chapple, Iain
Abstract : Neutrophils from PLS patients exhibit functional abnormalities possibly explaining pre-pubertal periodontitis, in their disease. Abstract: Papillon-Lefévre syndrome is a rare, inherited, autosomal-recessive disease, characterized by palmoplantar keratosis and severe prepubertal periodontitis, leading to premature loss of all teeth. Papillon-Lefévre syndrome is caused by a mutation in the cathepsin C gene, resulting in complete loss of activity and subsequent failure to activate immune response proteins. Periodontitis in Papillon-Lefévre syndrome is thought to arise from failure to eliminate periodontal pathogens as a result of cathepsin C deficiency, although mechanistic pathways remain to be elucidated. The aim of this study was to characterize comprehensively neutrophil function in Papillon-Lefévre syndrome. Peripheral blood neutrophils were isolated from 5 patients with Papillon-Lefévre syndrome, alongside matched healthy control subjects. For directional chemotactic accuracy, neutrophils were exposed to the chemoattractants MIP-1α and fMLP and tracked by real-time videomicroscopy. Reactive oxygen species generation was measured by chemiluminescence. Neutrophil extracellular trap formation was assayed fluorometrically, and proinflammatory cytokine release was measured following overnight culture of neutrophils with relevant stimuli. Neutrophil serine protease deficiencies resulted in a reduced ability of neutrophils to chemotax efficiently and an inability to generate neutrophil extracellular traps. Neutrophil extracellular trap-bound proteins were also absent in Papillon-Lefévre syndrome, and Papillon-Lefévre syndrome neutrophils released higher levels of proinflammatory cytokines in unstimulated and stimulated conditions, and plasma cytokines were elevated. Notably, neutrophil chemoattractants MIP-1α and CXCL8 were elevated in Papillon-Lefévre syndrome neutrophils, as was reactive oxygen species formation. We propose that relentless recruitment and accumulation of hyperactive/reactive neutrophils (cytokines, reactive oxygen species) with increased tissue transit times into periodontal tissues, alongside a reduced antimicrobial capacity, create a locally destructive chronic inflammatory cycle in Papillon-Lefévre syndrome.